Kwestia tajemniczego autorstwa renesansowego poematu Sarca - Kowalczyk-Cantoro, Daria (Przestrzenie Teorii, 2023)
Dating to the 1530s, the Latin poem Sarca was published in 1842 in Rome by Angelo Mai based on a manuscript found in Vienna. Forty years after publication, the incompatibility of this edition with the Viennese manuscript was first noticed. In the second half of the last century, a polemic began challenging the theory, previously considered certain, that Sarca’s author was Pietro Bembo. Researchers named Girolamo Fracastor, Andrea Navager and Agostino Beazzan, among others, as possible authors of the text in addition to Bembo. The question of the poem’s authorship remains unresolved to this day. The aim of this article is to analyse the turbulent and hypothesis-rich debate on the attribution of the Renaissance work. The poem has been subjected to internal criticism, i.e. inferences about the author’s person based on content analysis. Historical and bibliographical indicators of the work have also been examined. The article also attempts to answer the question of whether the latest techniques used in the analysis of the linguistic and stylistic features of the text, such as the methods of computer stylometry, could prove helpful in determining the authorship of the Sarca poem.